Analisis Pendapatan Usahatani Semangka (Citrullus Lanatus) Di Desa Tungkaran Kecamatan Martapura Kabupaten Banjar - Suratman, Yan Yozef Agus; Fitriadi, Subhan; Khaironi, Muhammad (Chlorophyl, 2023)
This research aims are : (1). Knowing the technical desription of water melon carrier out by farmer; (2). knowing the cost, revenues and income of water melon farming in Tungkaran Village, Martapura District, Banjar Regency.  This research uses survey method with observation technique.  This sampling method use saturated simple, namely taking water melon farmers who cultivate seedless water melons is only one person and is taken as a sample farmer. The result of the research is that the area of land use by farmer is 0.75 he and the status of the land is leased.  Production is 10,500 kg/farmer or 14,00 tons/ha.  The amount of explicit costs is IDR 26,935,433,33/farmer, revenue is  IDR 57,750,000.00/farmer, income is IDR 30,814,566.67/farmer